2022
DOI: 10.3390/diagnostics12020450
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Barrier Effect of the Physis against Metaphyseal Osteosarcoma: A Comprehensive Pathological Study with Its Radiological and Clinical Follow-Up Correlations

Abstract: Osteosarcoma is a primary malignant bone tumor usually arising at the metaphysis of long bones, particularly around the knee. The physis has been regarded as a barrier capable of blocking tumor extension, thus allowing it to preserve their epiphysis and therefore improve functional results. With the objective of clarifying how effective the physis is as a barrier to tumor spread, a large series of skeletally immature patients with osteosarcoma were reviewed. From 452 metaphyseal osteosarcomas a selection of 28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The rich vascular network provides sufficient oxygen and nutrients to tumor cells, and it is also a gateway for tumor metastasis, so the ability of angiogenesis is considered to be one of the markers of tumor aggressiveness. Tumor neovascularization plays an important role in the occurrence, development, invasion, and metastasis of osteosarcoma [ 10 , 11 ]. Understanding angiogenesis in osteosarcoma can help predict the prognosis of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The rich vascular network provides sufficient oxygen and nutrients to tumor cells, and it is also a gateway for tumor metastasis, so the ability of angiogenesis is considered to be one of the markers of tumor aggressiveness. Tumor neovascularization plays an important role in the occurrence, development, invasion, and metastasis of osteosarcoma [ 10 , 11 ]. Understanding angiogenesis in osteosarcoma can help predict the prognosis of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The same pronounced VEGF expression was found in tumours that crossed the physis. 15 These findings suggest that neovascularization is a relevant pathological change that helps tumour cells to cross the physis. The obtained results open the possibility of treating metaphyseal osteosarcoma with anti-angiogenic therapies, to halt the osteosarcoma invasion through the physis.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…We found 73% (73 patients) of disease-free survival in osteosarcoma and 68% (47 patients) in Ewing's sarcoma at a mean follow-up of 15 years versus 59% in those cases in which the epiphysis could not be preserved. 15 In addition, patients whose epiphyses could not be preserved had more metastases at diagnosis. Both datasets suggest the important role of an early diagnosis.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…This might result in longer patient delay and thus larger tumor size and more frequent metastases at time of diagnosis. In pediatric osteosarcoma and ES, time from initial symptoms to start of treatment matters in terms of survival and local recurrence rates [33,34]. However, in both osteosarcoma and ES, it has also been suggested that treatment delay would not influence outcome, so maybe biological behavior of these malignancies is more important for prognoses [35,36].…”
Section: Discussionmentioning
confidence: 99%